Level and change in bone microarchitectural parameters and their relationship with previous fracture and established bone mineral density loci - Fuggle, Nicholas R.; Westbury, Leo D.; Bevilacqua, Gregorio; Titcombe, Philip; Ó Breasail, Mícheál; Harvey, Nicholas C.; Dennison, Elaine M.; Cooper, Cyrus; Ward, Kate A. (Bone (New York, N.Y.), 2021)
Osteoporosis is characterised by a reduction of bone mineral density (BMD) and predisposition to fracture. Bone microarchitecture, measured by high resolution peripheral quantitative computed tomography (HR-pQCT), has been related to fragility fractures and BMD and has been the subject of large-scale genome-wide analysis. We investigated whether fracture was related to baseline values and longitudinal changes in bone microarchitecture and whether bone microarchitecture was associated with established BMD loci. 115 males and 99 females (aged 72–81 at baseline) from the Hertfordshire Cohort Study (HCS) were analysed. Fracture history was determined in 2011–2012 by self-report and vertebral fracture assessment. Participants underwent HR-pQCT scans of the distal radius and tibia in 2011–2012 and 2017. Previous fracture in relation to baseline values and changes in tibial HR-pQCT parameters was examined using sex-adjusted logistic regression with and without adjustment for age, sociodemographic, lifestyle and clinical characteristics; baseline values and changes in parameters associated with previous fracture were then examined in relation to four established BMD loci after adjustment for sex and age. Previous fracture was related to: higher trabecular area (fully-adjusted odds ratio [95% CI] per SD greater baseline value: 2.18 [1.27,3.73], p = 0.005); lower total volumetric BMD (0.53 [0.34,0.84], p = 0.007), cortical area (0.53 [0.30,0.95], p = 0.032), cortical BMD (0.56 [0.36,0.88], p = 0.011) and cortical thickness (0.45 [0.27,0.77], p = 0.004); and greater declines in trabecular BMD (p = 0.001). Associations were robust in sex- and fully-adjusted analysis. Relationships between BMD loci and these HR-pQCT parameters were weak: rs3801387 (WNT16) was related to decline in trabecular BMD (p = 0.011) but no other associations were significant (p > 0.05). Baseline values of HR-pQCT parameters and greater decline in trabecular BMD were associated with fracture. Change in trabecular BMD was associated with WNT16 which has been demonstrated to influence bone health in murine models and human genome-wide association studies (GWAS). [Display omitted] •Data from participants of the Hertfordshire Cohort Study (aged 72–81) were analysed.•Bone parameters were examined in relation to previous fracture and BMD loci.•Previous fracture was related to baseline values of several HR-pQCT parameters.•Previous fracture was only related to changes in trabecular BMD.•Relationships between BMD loci and HR-pQCT parameters were weak.